3D.01: VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY INCREASES RISK OF STROKE OR CARDIAC EVENTS IN PATIENTS GIVEN VALSARTAN OR AMLODIPINE IN THE VALUE TRIAL. (June 2015) - Mehlum, M.; Liestøl, K.; Julius, S.; Kjeldsen, S.E.; Hua, T.A.; Rothwell, P.M.; Mancia, G.; Parati, G.; Weber, M.A.; Berge, E.
Abstract : Objective: High blood pressure variability has been associated with an increased risk of cardiovascular events. We aimed to assess if increased visit-to-visit variability in systolic blood pressure increases the risk of stroke or cardiac events (fatal/non-fatal coronary or heart failure events) in the VALUE population. Design and method: The VALUE trial was a randomised-controlled, double-masked investigation of valsartan versus amlodipine in patients 50 years or older with hypertension and high risk of cardiovascular events. Mean follow-up time was 4.2 years. We calculated the standard deviation (SD) of mean systolic blood pressure from visits from 6 months onward, excluding patients with less than 2 visits, or stroke or cardiac events during the first 6 months. In the pooled treatment arms, we grouped SD in quintiles and compared the risk of stroke or cardiac events in the highest and the lowest quintile, using a Cox regression model, adjusting for a number of prognostic variables, including randomised treatment and mean BP from 6 months onwards. Results: Of 14.146 patients included, 1278 (9.0%) experienced a cardiac event and 473 (3.3%) experienced a stroke. Compared to patients with the lowest variability, those in the highest quintile had an increased risk of stroke or cardiac events (HR 1.4, 95% CI 1.0–1.8, p = 0.045 and HR 1.9, 95% CI 1.6–2.3, p < 0.0001, respectively, Figure). Conclusions: Visit-to-visit systolic BP variability predicts stroke and cardiac events in high risk hypertensive patients receiving valsartan or amlodipine, and independent of mean BP. Systolic blood pressure variability was a stronger predictor of cardiac events than of stroke. Figure. No caption available.